How capping protein enhances actin filament growth and nucleation on biomimetic beads. (23rd November 2015) - Wang, Ruizhe; Carlsson, Anders E
Abstract: Capping protein (CP), which caps the growing ends of actin filaments, accelerates actin-based motility. Recent experiments on biomimetic beads have shown that CP also enhances the rate of actin filament nucleation. Proposed explanations for these phenomena include (i) the actin funneling hypothesis (AFH), in which the presence of CP increases the free-actin concentration, and (ii) the monomer gating model, in which CP binding to actin filament barbed ends makes more monomers available for filament nucleation. To establish how CP increases the rates of filament elongation and nucleation on biomimetic beads, we perform a quantitative modeling analysis of actin polymerization, using rate equations that include actin filament nucleation, polymerization and capping, as modified by monomer depletion near the surface of the bead. With one adjustable parameter, our simulation results match previously measured time courses of polymerized actin and filament number. The results support a version of the AFH where CP increases thelocal actin monomer concentration at the bead surface, but leaves the global free-actin concentration nearly constant. Because the rate of filament nucleation increases with the monomer concentration, the increased local monomer concentration enhances actin filament nucleation. We derive a closed-form formula for the characteristic CP concentration where the local free-actin concentration reaches half the bulk value, and find it to be comparable to the global Arp2/3 complex concentration. We also propose an experimental protocol for distinguishing branching nucleation of filaments from spontaneous nucleation.